The Bacterial Two-Hybrid System Uncovers the Involvement of Acetylation in Regulating of Lrp Activity in Salmonella Typhimurium - Qin, Ran; Sang, Yu; Ren, Jie; Zhang, Qiufen; Li, Shuxian; Cui, Zhongli; Yao, Yu-Feng (Frontiers in Microbiology, 2016)
Nε-lysine acetylation is an abundant and important Post-translational modification in bacteria. We used the bacterial two-hybrid system to screen the genome library of the Salmonella Typhimurium to identify potential proteins involved in acetyltransferase Pat - or deacetylase CobB-mediated acetylation. Then, the in vitro (de)acetylation assays were used to validate the potential targets, such as STM14_1074, NrdF, RhaR. Lrp, a leucine-responsive regulatory protein and global regulator, was shown to interact with Pat. We further demonstrate that Lrp could be acetylated by Pat and deacetylated by NAD+-dependent CobB in vitro. Specifically, the conserved lysine residue 36 (K36) in helix-turn-helix (HTH) DNA-binding domain of Lrp was acetylated. Acetylation of K36 impaired the function of Lrp through altering the affinity with the target promoter. The mutation of K36 in chromosome mimicking acetylation enhanced the transcriptional level of itself and attenuated the mRNA levels of Lrp-regulated genes including fimA, which was confirmed by yeast agglutination assay. These findings demonstrate that the acetylation regulates the DNA-binding activity of Lrp, suggesting that acetylation modification of transcription factors is a conserved regulatory manner to modulate gene expression in bacteria and eukaryotes.